[Rainbow Over Gullfoss] - Streng, Evelyn Fiedler (1975)
Photograph of a rainbow over Gullfoss Waterfall. The grey waterfall is short and wide, falling in layers over rock ledges. A rock ledge sits to the left, the rainbow ending on it. Green, rounded hills and plateaus are dotted with brown rocks surrounding the water.